2019
DOI: 10.1089/hum.2018.234
|View full text |Cite
|
Sign up to set email alerts
|

Five Years of Successful Inducible Transgene Expression Following Locoregional Adeno-Associated Virus Delivery in Nonhuman Primates with No Detectable Immunity

Abstract: Anti-transgene immune responses elicited after intramuscular (i.m.) delivery of recombinant adenoassociated virus (rAAV) have been shown to hamper long-term transgene expression in large-animal models of rAAV-mediated gene transfer. To overcome this hurdle, an alternative mode of delivery of rAAV vectors in nonhuman primate muscles has been described: the locoregional (LR) intravenous route of administration. Using this injection mode, persistent inducible transgene expression for at least 1 year under the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 68 publications
0
27
1
Order By: Relevance
“…Also, from a clinical perspective, particularly attractive would be the ability to not only express the scFv but to switch it on or off at will, adding a layer of exogenous control to improve safety. Among the currently available inducer/repressor systems permitting control over gene expression, the tetracycline (Tet)-dependent system is by far the most advanced and most widely used, and has been already tested in association with AAV1 and locoregional muscle gene transfer in non-human primates showing no humoral or cellular responses against the transgene [ 94 ]: we will certainly explore this avenue in our system.…”
Section: Discussionmentioning
confidence: 99%
“…Also, from a clinical perspective, particularly attractive would be the ability to not only express the scFv but to switch it on or off at will, adding a layer of exogenous control to improve safety. Among the currently available inducer/repressor systems permitting control over gene expression, the tetracycline (Tet)-dependent system is by far the most advanced and most widely used, and has been already tested in association with AAV1 and locoregional muscle gene transfer in non-human primates showing no humoral or cellular responses against the transgene [ 94 ]: we will certainly explore this avenue in our system.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, GpG‐enriched pDNA has been shown to protect against anti‐transgene immune response . To date, gene therapy pre‐clinical studies (in animal models) have shown no induction of any deleterious immune reaction against the transgene following HLV injection . However, this remains to be confirmed in humans.…”
Section: Other Miscellaneous Considerationsmentioning
confidence: 98%
“…A non‐viral gene therapy protocol based on the HLV delivery of an EPO‐encoding pDNA was evaluated in SM of subtotal nephrectomied Lewis rats and in rhesus monkeys . Long‐term inducible transgene expression (for at least 5 years) of an EPO‐encoding pDNA was also shown in non‐human primates using an AAV vector delivered by HLV injection; no deleterious immune reaction against the transgene could be detected throughout the duration of the study …”
Section: Hlv Gene Delivery: Interests and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, higher cellular concentrations of Cas9 have been shown to decrease specificity, presumably because off-target cleavage is the only possibility after all target sites have been destroyed (Davis et al, 2015). This observation has raised concerns for therapeutic developments that rely on viral gene transfer, which in the case of AAVmediated gene expression, persists for several years after delivery (Nathwani et al, 2011;Wojno et al, 2013;Colella et al, 2018;Guilbaud et al, 2019). Engineered ribonucleoprotein complexes (RNP; Cas9 protein bound to a guide RNA) and Cas9-encapsulating nanoparticles have been developed as non-viral alternatives for local, transient CRISPR expression in the brain.…”
Section: Gene Disruption In the Mammalian Brain Via Crispr-cas And Nhejmentioning
confidence: 99%